Evaluation of The Effect of Crude Extracts of Fenugreek on Resistant Isolates of Candida species (In vitro study) - Murtadha Abdullah Abbood; Azhar A. F. AL- Attraqchi; Hayder B. Sahib (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: The recent emergence of fungal resistance strains has caused concern in medical settings. Medicinal plants continue to be viable sources of bioactive chemicals with therapeutic potential. These compounds can be extracted in different techniques using various solvents that give rise to a wide variety of extracted bioactive compounds that act as anti-fungal. The research aimed to evaluate the effect of fenugreek seed extracts on resistant isolates of Candida spp. isolated from sever COVID-19 patients.Methodology: The study was conducted from August 2021 to November 2022 at Al-Imam AlHussein Medical City and Al-Hayat Respiratory Diseases Units. Under a specialist's physician's supervision, severe COVID-19 cases were collected. The collected 455 sputum samples were examined directly and cultured on Sabouraud′s Dextrose agar (SDA) media; growth colonies were distinguished and used Grams stain with the API system before the antifungal susceptibility test was performed in accordance with clinical and laboratory standards institute (CLSI 2020) by disc diffusion method to differentiate the resistance microorganism. The extraction process was conducted using the soxhlet technique (100 grams of seed powder and 800 milliliters of solvents (chloroform, methanol, and water) for eight hours. Electrical rotatory evaporators were used to evaporate the extract to get the concentrated crude extracts. FTIR and GCMS instruments used to detection of bioactive compounds in crude fenugreek seed extracts(aqueous, methanol, and chloroform).Then, different concentrations of each extract (25, 50, 100, and 150 mg/ml) and their effect against the tested resistance study isolated were examined by well diffusion method and Minimum inhibitory concentration was measured.Results: A 455 were enrolled in this study. Patients' ages ranged from 20 to 91 years (mean 52.23, SD 15.009). This study indicated that more than half of the samples were males [(262) 57.6%] and [(193)42.4%] were females.The FTIR and GC-MS showed the methanolic extract potent the most bioactive compounds, followed by the chloroform and water extracts. Evaluation of antimicrobial effects at 50 mg/ml, the methanolic extract showed the greatest effect, with a mean inhibition zone of 9.33 mm and a significant value of 0.01; at 100 mg/ml, the chloroform extract showed the next greatest effect, with a mean inhibition zone of 10.33 mm and a significant value of 0.005. At 150 mg/ml, the aqueous extracts showed the least effect, with a mean inhibition zone of 8.33 mm and a non-significant value of 0.024. Conclusions: Candida spp. were most frequent isolated yeast from sputum of patients with severe COVID-19. Methanol extract was the most effective anti-candida, followed by chloroform extract, and the aqueous extract was the least effective. The most effective anti-candida drug is ketoconazole.